GESTÃO SOCIAL E CIDADANIA: ENSINO, PESQUISA E EXTENSÃO - Allebrandt, Sergio Luis; Silva, Elizandra Pinheiro Da; Basso, Lauri; Formentini, Marcia; Rasia, Pedro Carlos; Albarello, Sandra Regina (Salão do Conhecimento, 2019)
PROJETO DE EXTENSÃO GESTÃO SOCIAL E CIDADANIA